Intense pulsed light therapy (IPL) induced iritis following treatment for a medial canthal capillary malformation. (14th January 2014) - Crabb, Matthew; Chan, Weng Onn; Taranath, Deepa; Huilgol, Shyamala C
Abstract The popularity of intense pulsed light (IPL) therapy continues to increase due to its relative safety, high skin coverage rate and ability to treat both vascular and pigmented lesions. An often‐overlooked risk is the potential for IPL‐induced ocular damage. The damage sustained can cause significant, persistent morbidity and can occur even with very limited IPL exposure to the eye.